The Effect of Work Stress and Workload on Employee Performance at Cv. Karya Tani Kamanre - Alpriani; Haedar; Ilham Tahier (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the Effect of Job Stress and Workload on Employee Performance at CV. Karya Tani Kamanre. The research method used in this study is a quantitative approach. The sampling technique applied is a saturated sampling technique, namely the entire population is used as a sample, consisting of 30 respondents. The data analysis technique used is multiple linear regression. The results of this study reveal that 1. Job stress has a positive and significant effect on employee performance. 2. Workload does not have a positive and significant effect on employee performance. 3. Simultaneous testing shows that job stress and workload simultaneously have an effect on employee performance.